Metal catalyst-assisted growth of GaN nanowires on graphene films for flexible photocatalyst applications - Park, Jun Beom; Kim, Nam-Jung; Kim, Yong-Jin; Lee, Sang-Hyup; Yi, Gyu-Chul (Current applied physics, 2014)
We report the growth of high-areal-density GaN nanowires on large-size graphene films using a nickel (Ni) catalyst-assisted vapor-liquid-solid (VLS) method. Before the nanowire growth, the graphene films were prepared on copper foils using hot-wall chemical vapor deposition and transferred onto SiO2/Si substrates. Then, for catalyst-assisted VLS growth, Ni catalyst layers with thickness of a few nanometers were deposited on the graphene-coated substrates using a thermal evaporator. We investigated the effect of the Ni catalyst thickness on the formation of GaN nanowires. Furthermore, the structural and optical characteristics of GaN nanowires were investigated using X-ray diffraction, transmission electron microscopy, and photoluminescence spectroscopy. The GaN nanowires grown on graphene films were transferred onto polymer substrates using a simple lift-off method for applications as flexible photocatalysts. Photocatalysis activities of the GaN nanowires prepared on the flexible polymer substrates were investigated under bending conditions.